Reserves were not so ample after all - Adam Copeland; Darrell Duffie; Yilin Yang (Federal Reserve Bank of New York, 2021)
The Federal Reserve's "balance-sheet normalization," which reduced aggregate reserves between 2017 and September 2019, increased repo rate distortions, the severity of rate spikes, and intraday payment timing stresses, culminating with a significant disruption in Treasury repo markets in mid-September 2019. We show that repo rates rose above efficient-market levels when the total reserve balances held at the Federal Reserve by the largest repo-active bank holding companies declined and that repo rate spikes are strongly associated with delayed intraday payments of reserves to these large bank holding companies. Intraday payment timing stresses are magnified by early-morning settlement of Treasury security issuances. Substantially higher aggregate levels of reserves than existed in the period leading up to September 2019 would likely have eliminated most or all of these payment timing stresses and repo rate spikes.
Keywords: G14; D47; D82; 330; repo rates; reserves; Treasuries; payments; central bank balance sheet